Oral submucosal fibrosis: a comprehensive review on pathogenesis, diagnosis, therapeutics and computational advances - Mokal, Chinmay Nitin.; Das, Mrinmoy; Hannenhalli, Sridhar; Agrawal, Piyush (Frontiers in Cell and Developmental Biology, 2026)
Oral submucosal fibrosis (OSF) is a chronic and progressive fibrosis disease and causes sclerosis in oral mucosal tissue with a higher potential of malignant transformation. It is characterized by excessive production and deposition of extracellular matrix. The major behavioral cause of OSF is chewing areca nut, and the symptoms include severe burning sensation, ulceration, restricted mouth opening, and more. However, despite significant advancements in biochemical and molecular techniques in recent years, no specific and targeted antifibrotic treatment strategies have been approved, potentially due to the complicated molecular mechanism that initiates and drives the fibrotic events, which remains to be completely understood. In this review, we aimed to discuss the epidemiology, etiology, and risk factors associated with the OSF, with special emphasis on the recent developments such as the use of flavored areca nut, etc. Then we highlight the OSF pathogenesis with special emphasis on the role of TGF-b, epithelial-mesenchymal transition, and other processes such as dysregulation of collagen metabolism and angiogenesis. We also mentioned the role of hypoxia-induced pathogenesis, which recently has been more in focus. Next, apart from traditional diagnosis methods, i.e., clinical evaluation and histopathology, we also discussed newer techniques such as biomarkers present in serum, saliva, and tissue biopsies. Afterwards, we mention ongoing traditional and modern treatments in clinical settings, such as the use of natural compounds, anti-fibrotic agents, targeted therapy, and more. We also discussed the role of emerging new therapeutic targets and how targeting them can overcome the current limitations. Moving ahead, we discussed how next-generation sequencing and artificial intelligence have improved our understanding of OSF pathophysiology. We conclude with a discussion of future perspectives and potential ways for developing novel OSF treatment or management.